Modèle énergétique uniboite de la croissance des huîtres ( Crassostrea gigas) dans le bassin de Marennes-Oléron - Bacher, C.; Héral, M.; Deslous-Paoli, J. M.; Razet, D. (Canadian Journal of Fisheries and Aquatic Sciences, 1991)
The growth of oysters (Crassostrea gigas) is modeled in order to study the trophic capacity of the Bay of Marennes-Oléron. Total seston and amount of protids, lipids, and carbohydrates converted to energy are the environmental factors taken into account. Time series of these variables are derived during 2 yr with a daily time step from a linear regression including the tidal velocity, the height of the water column, and the wind velocity. A model of the energetic budget based on assimilation and respiration terms and depending on the previous time series is run to simulate the individual growth of an oyster. The knowledge of the number of oysters, the flow of water entering the bay, and the volume of the bay allows us then to estimate that 7% of the available energy is used by the population. The number of individuals is given theoretical values to show that the impact of the amount of oysters on the growth of an individual is nonnegligible. The trophic capacity of the bay is then defined and it is pointed out that more information may be expected from a model coupling the transport of particulate matter and the growth of oysters.